2019
DOI: 10.2106/jbjs.19.00073
|View full text |Cite
|
Sign up to set email alerts
|

Subluxation of the Middle Facet of the Subtalar Joint as a Marker of Peritalar Subluxation in Adult Acquired Flatfoot Deformity

Abstract: Background: Progressive peritalar subluxation (PTS) is part of adult acquired flatfoot deformity (AAFD). We investigated the use of the middle facet as an indicator of PTS using standing, weight-bearing computed tomography (CT) images. We hypothesized that weight-bearing CT would be an accurate method of measuring increased subluxation (“uncoverage”) and incongruence of the middle-facet among patients with AAFD. Methods: We included 30 patients with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 20 publications
1
78
1
Order By: Relevance
“…In an 8-year cohort study, Christine L et al [ 32 ] found that weight gain was positively correlated with the risk of falling. Studies have shown that a higher BMI in older women increases their risk of falling; weight gain is closely related to hormonal changes in postmenopausal women, an increase in the incidence of flatfoot and a decline in lower-limb muscle quality [ 33 , 34 ]. Obese elderly women have high lean leg masses but lack muscle strength, so they have poor balance and stability and are prone to falls [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an 8-year cohort study, Christine L et al [ 32 ] found that weight gain was positively correlated with the risk of falling. Studies have shown that a higher BMI in older women increases their risk of falling; weight gain is closely related to hormonal changes in postmenopausal women, an increase in the incidence of flatfoot and a decline in lower-limb muscle quality [ 33 , 34 ]. Obese elderly women have high lean leg masses but lack muscle strength, so they have poor balance and stability and are prone to falls [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,8,10-12,14,15,22 Both measurements, PTS and FAO, were found to be reliably assessed in patients with AAFD. 1,7,8,10,11,14,15,22…”
Section: Discussionmentioning
confidence: 89%
“…14,15 The potential importance of using the middle facet of the subtalar joint to identify PTS in patients with AAFD has been neglected until a recent study by de Cesar Netto and colleagues. 8 In this case-control study involving 30 patients with AAFD and 30 paired controls, the authors assessed middle facet coronal plane PTS at its anteroposterior midpoint by measuring the percentage of joint uncoverage and the incongruence angle between the opposing articular surfaces. They demonstrated an extremely high diagnostic accuracy for symptomatic AAFD using both middle facet measurements, with values of joint uncoverage above 17.9% showing a 100% specificity and 96.7% sensitivity, and incongruence angle measurements higher than 8.4 degrees providing 100% specificity and 100% sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, the middle facet is used as an isolated marker for PTS, with a mean subluxation (uncoverage) of approximately 45% in symptomatic patients with PCFD and 5% among controls. 8 Measurement of the amount of linear subluxation of the subtalar joint at the posterior facet in the coronal plane has also been proposed to indicate PTS, 7,9,30 but it was found to be less reliable. 9 Lateral subluxation was reported to cause sinus tarsi and subfibular impingement.…”
Section: Rationalementioning
confidence: 99%